Sleep Disturbances in COPD are Associated with Heterogeneity of Airway Obstruction. (4th July 2018) - Basile, Marco; Baiamonte, Pierpaolo; Mazzuca, Emilia; Principe, Stefania; Pennavaria, Federica; Benfante, Alida; Scichilone, Nicola
Abstract: Individuals with Chronic Obstructive Pulmonary Disease (COPD) experience sleep disturbances due to the impact of respiratory symptoms on sleep quality. We explored whether sleep disturbances in COPD are linked to heterogeneity of airway constriction. The impact of breathing problems on sleep quality was measured in consecutive COPD outpatients with the COPD and Asthma Sleep Impact Scale (CASIS) questionnaire. Impulse oscillometry technique (IOS) was employed to assess heterogeneity of airway constriction. Subjects with a previous or concomitant diagnosis of asthma or obstructive sleep apnea (OSA) were excluded. Fifty COPD subjects (M/F 40/10; age: 71 ± 8 yrs, Body Mass Index (BMI): 26.2 ± 4.7 kg/m 2, Forced Expiratory Volume in the first second (FEV1 ): 65 ± 25% predicted; mean ± SD) were enrolled. The mean CASIS score was 36 ± 3.3, and the R5–R20 value was 0.2 ± 0.15 kPa s L −1 . The CASIS score was significantly higher in subjects with increased R5–R20 (>0.07 kPa s L −1 ) (39 ± 24; p = 0.02) compared to normal R5–R20 (21 ± 17). When subjects were categorized on the basis of lung function in severely versus non severely obstructed (FEV1 ≤ or >50% predicted) or air trappers versus non air trappers (Residual Volume, RV ≥ or <120% predicted) the CASIS score remained unchanged (for FEV1 : 37 ± 23 versus 33 ± 25, respectively, p  = 0.61; for RV: 30 ± 20 versus 40 ± 23, p  = 0.16). Sleep disturbances due to COPD symptoms are associated with heterogeneity of airway constriction, possibly reflecting peripheral airway dysfunction.